Ensuring Halal Product Integrity and an Investigative Study of U.S Policy Practices - Rahman, Md Mahfujur; Ahmad, Zaki (Riviera Publishing, 2024)
Anticipating a significant rise to 27% of the global population by 2030, the halal industry is garnering noteworthy attention worldwide. This study provides a comprehensive investigation of halal industrial players with the elements of products and the United States' regulatory landscape. It aims to scrutinize the hurdles faced by the halal industry and gauge the effectiveness of prevailing policies. The research methodology encompasses a series of phone interviews with industry experts, complemented by extensive desktop research encompassing research papers, articles, journals, textbooks, and news reports. This study is guided by three primary research objectives. It aims to gain insights from key industry stakeholders, understand non-halal elements in products beyond meat in the Muslim market, and evaluate halal industry policies in the United States, emphasizing their origins and the role of independent organizations in ensuring compliance. The findings illuminate prevalent policy adoption and underscore the paramount importance of standardized approaches and stringent oversight within the halal industry. Thus, the current research offers invaluable insights into the dynamic landscape of halal products and policies in the United States, enriching the ongoing discourse on the industry's trajectory and sustainability.